The Relationship Between Digital Literacy and Emotional Intelligence on Vocational High School Students' Work Readiness - Endeli Endeli; Hansi Efendi; Hendra Hidayat (Postgraduate, University of Mataram, 2025)
Vocational education plays a crucial role in preparing a skilled workforce to meet industrial demands. However, the high unemployment rate among vocational high school (SMK) graduates, reaching 8.62% in February 2024 (BPS), indicates a gap between graduates' competencies and industry requirements. This study aims to examine the relationship between digital literacy, emotional intelligence, and job readiness among vocational students in Kabupaten Lima Puluh Kota. This research employed a quantitative approach with data collected through questionnaires and tests administered to 195 students from SMK Negeri 1 Guguak and SMK Negeri 2 Guguak. Multiple regression analysis was used to evaluate the impact of digital literacy and emotional intelligence on job readiness. The results show that digital literacy significantly influences job readiness (t-value = 6.568, p < 0.05), highlighting the importance of mastering digital tools for employability. Similarly, emotional intelligence has a significant effect (t-value = 1.804, p < 0.05), demonstrating its role in workplace adaptability and collaboration. Furthermore, both variables collectively contribute to job readiness (F-value = 28.623, p < 0.05), explaining 54.9% of its variance. Moreover, strengthening digital literacy and emotional intelligence also supports the development of STEAM-based competencies, which are essential for preparing vocational students for the dynamic demands of the modern workforce. These findings emphasize the need for integrating digital literacy and emotional intelligence training in vocational education to enhance graduates' competitiveness in the labor market